Stem Cells and Therapy: Emerging Approaches - Manuela Monti (European Journal of Histochemistry, 2020)
The ten chapters of this volume exploit the potentials of stem cells biology in translational medicine in a very clear way also thanks to nice color illustrations together with tricks and suggestions useful to get reproducible results...